The Ethics of Detachment in Santayana's Philosophy - Brodrick, M. author. aut Link
VIII, 174 p.
Keywords: Knowing that we are finite, how can we live to the fullest? Philosopher George Santayana suggested 'spirituality' enables us to enjoy what we have. This book clarifies and extends Santayana's account of spirituality, while suggesting how the detachment of spirituality can relieve human suffering, enrich our lives, and make us better human beings.